Islamophobia in South Korea with a focus on Muslim migrants - Han, Sang Yong (AUC Knowledge Fountain, 2017)
Much academic research has analyzed the issue of Islamophobia and how Muslims are often represented in a negative or stereotypical way in Western countries. There is little research focusing on this phenomenon in East Asia, and specifically, in South Korea. This thesis attempts to fill this gap by shedding light on this particular topic in South Korea, in explaining why Islamophobic attitudes were particularly pervasive among certain sectors including right wing politicians and Protestants in the country between 2014 and 2016. Despite the visible presence of a Muslim minority since the 1990s in South Korea a decade before 9/11, the debate that Muslims could be a potential security or cultural threat and thus should be assimilated into the relatively homogenous Korean society has prevailed. This case study is important because Islamophobic sentiments, such as negative perceptions and prejudices against Islam and Muslims, have recently spread in the South Korean society affecting the Muslim minority in the aftermath of 9/11, and following an incident where Korean citizens were kidnapped by the Taliban in Afghanistan in 2007. This phenomenon has been further fueled by a series of interconnected terror attacks throughout the world mainly conducted or inspired by ISIS since 2014. The research for this thesis is based on an in-depth discourse analysis of the roots of Islamophobic discourse in South Korea with special reference to securitization theory, which posits that the analysis of issues through the frame of security contributes to the creation of hostile public discourse and places national interests above other issues like tolerance and acceptance. It also investigates how security and political discourses regarding Muslims have been formulated, followed by an analysis of the social discourse, media coverage, and online discourse. This thesis deals with online discourse by exploring the nature of Islamophobic attitudes via a case study on Twitter and the religious discourse by looking in detail at Christian-Muslim relations.